Investigating Soil Fertility Dynamics in Expanding Agricultural Regions of Iraq’s Western Desert - Alalwany, AbdulKarem A. M.; Al-Shaye’, Oqba Nafia Abdulaziz (Agricultural Sciences: Techniques and Innovations Vol. 1, 2025)
The world’s population now stands at 7 billion and could exceed 9 billion in 2050, leading to an increase in demand for world food. The total area of the land includes marginal lands, such as deserts, high mountains, swamps, and arable areas. Sustainable management of soil has become a necessity. Agricultural expansion is the main pillar for increasing agricultural production and for agricultural development, with multiple mechanisms and successive implementation procedures. The agricultural expansion plans for any area require a scientific study of all land resources, economic and social conditions, water resources, soil fertility, climatic conditions, optimum utilisation and mapping of the fertility status of the study areas. The objective of this study is to evaluate some of the desert soils to be developed in the future and to know the critical boundaries of the available major nutrients and some minor elements, and to make recommendations that guide investment operations and agricultural expansion in western Iraq. The preparation of such studies requires a field survey of these resources based on previous studies in soil and geology. Therefore, the current work is an attempt to develop a database on these soils in the case of future investment. The study included the implementation of a survey of the culture in the period from February 2012 to January 2013 for three areas within the Western desert environment: Dum Al Ksfa, Dum Al Shamia and Dum Gbab Western: 11,480, 27,120, 140,840 square dunam, respectively. Morphological, physical and chemical tests of the surface layer soil samples for more than 10 auger holes for each site and three pedons representing each region were studied. In addition climate change during all months of the year was monitored. The study concluded that, based on the climatic data of the study areas, soil moisture is present in the dry climate of the Torric moisture regime, and the temperature of the soil within the hyperthermic range belongs to the soil of the study area to the Ardisols. The pH of the soil was slightly alkaline. The salinity of the soil of the study areas was that the soil of the Dum Al Shamia and Dum Gbab western area was normal. The average values of the major nutrients include total nitrogen (0.4- g/kg 0.6) and phosphorus (1.38-6.7mg.kg-1) and potassium (0.31-0.4cmol kg-1) and iron (0.5 mg/l), zinc (0.2-1.1 mg/l) copper (0.5-0.7 mg/l). Organic carbon was low in all regions under international critical limits. The soil in the region has a marginal potential for agricultural production, given the dry conditions and difficulty of agricultural exploitation in desert soils. The use of management methods will improve agricultural productivity and optimal production. Therefore, this study focuses on three areas within the Western Desert of Iraq. These areas were chosen for the study, with all possible recommendations for the conservation of arable land, which is one of the most scarce resources. However, a more detailed study and analysis of the studied soil should be undertaken to complement reliable results and to establish a database of land resources for the study area to assist decision-makers in developing sustainable agricultural development plans for the future.